PENGUATAN UMKM PENGOLAH DAN PEMASAR IKAN ASAP DI DESA FIDITAN - KOTA TUAL PROVINSI MALUKU - Ismael Marasabessy; Dani Sjafardan Royani; Syahibul Kahfi Hamid (LPPM UNIMA, 2022)
Partners of this science and technology application are the groups of smoked fish processing and marketing in Fiditan village, Tual city, Maluku province. The problems of the two partners include problems with the quality of fresh fish raw materials, traditional smoking technology (open stove smoking), poor packaging, and not being able to calculate operating profit and loss. The main objective of this activity is to empower groups of micro-businesses processing and marketing smoked fish, and in particular (1). Improving raw material handling technology, (2). Improving fish smoking technology, (3). Improving smoked fish packaging, (4). Organize the financial management of partners, and (5). Add online market. The approach method used is discussion and mentoring, counseling and training, and mentoring to strengthen technology transfer to partners. The results achieved indicate that the improvement of the quality of raw materials and continuity of production can be done by partners with the application of freezers, the use of smoking cabinets can increase the amount of production and can improve the sanitation and hygiene of the production process where cross contamination is reduced. Consumers are more interested in partner smoked fish products because with the application of packaging equipped with labeling, using 2 types of primary and secondary packaging, smoked fish products look more elegant and classier.